Possibilities For Improvement Of Pedagogical Work Of Teachers In The Process Of Further Education In The Conditions Of The Slovak Republic - Cabanová, Vlasta (Advances in Social Sciences Research Journal, 2015)
The present paper deals with the professional development of Slovak primary and secondary school teachers. The author provides the analysis of the qualification growth process and of expanding professional competencies in accordance with the latest scientific knowledge, social needs and requirements for the teaching performance in various institutions of Slovakia. It is realized in the form of actualized education ensuring the latest knowledge mediation, deepening, development and dissemination of professional and pedagogical knowledge and skills. Innovative education will enable improvement of the performance standard of pedagogical or professional activities. The author compares the possibilities of further education in Slovakia with the possibilities of further education in other countries on the basis of experience obtained during her participation in the international project Leonardo da Vinci No. 113421512.